Analysis of Law No. 19 Of 2016 on Consumer Protection in Digital Transactions on the Facebook Marketplace Sales System - Ahsanul Rizki; Budi Abdullah (SEAN Institute, 2025)
The development of information and communication technology has driven the growth of digital transactions, including through marketplace platforms such as Facebook Marketplace. However, alongside the increase in digital transactions, consumer protection has also become a significant challenge. This study aims to analyze the implementation of Law No. 19 of 2016 on Consumer Protection in digital transactions on the Facebook Marketplace platform. This research employs a qualitative approach with a case study method. Primary data were collected through in-depth interviews with consumers who were engaged in transactions via Facebook Marketplace, while secondary data were obtained from document analysis and references from journals published in the last four years. The findings reveal that although Law No. 19 of 2016 provides a strong legal foundation, its implementation is not yet optimal. The lack of consumer rights education and limited oversight resources are challenges that need to be addressed. This study recommends enhancing consumer rights education and awareness, improving the supervision of digital platform businesses, and refining consumer dispute resolution mechanisms to strengthen consumer protection in digital transactions.